(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2026)
A prevalent issue in the contemporary educational landscape is the disparity in educators’ proficiency in integrating technology within the classroom. Low student engagement and learning outcomes are often driven by the dominance of conventional lecture methods and the suboptimal utilization of digital technology to accommodate diverse learning styles. This study aims to analyze the improvement in learning activities and outcomes among seventh-grade students regarding the topic of Temperature and Expansion through the implementation of a digital-based differentiated learning approach. The research employs a quantitative quasi-experimental methodology featuring a one-group pretest-posttest design. The sample population consists of 23 students from Class VII A. Data collection methods include observational techniques, interviews, questionnaires, and evaluative test items. The instructional media utilized comprise teaching modules, student worksheets, and digital learning platforms. Analytical techniques involve instrument testing, learning outcome assessment, student activity evaluation, and N-Gain analysis. The findings reveal that the average score for all student activity indicators reached 87.88%, placing it in the "very high" category. Furthermore, the results demonstrate a significant increase in student learning outcomes following the implementation of the digital-based differentiated learning approach, evidenced by an N-Gain score of 0.72, which falls into the "high" category. This underscores the effectiveness of the digital-based differentiated learning approach in enhancing students’ academic performance related to the subject of temperature and expansion.